Changes in sleeping energy metabolism and thermoregulation during menstrual cycle. Issue 2 (24th January 2020) - Zhang, Simeng; Osumi, Haruka; Uchizawa, Akiko; Hamada, Haruka; Park, Insung; Suzuki, Yoko; Tanaka, Yoshiaki; Ishihara, Asuka; Yajima, Katsuhiko; Seol, Jaehoon; Satoh, Makoto; Omi, Naomi; et al.
Abstract: Women with ovulatory menstrual cycles show an increase in body temperature in the luteal phase, compared with follicular phase, particularly during the night. Several, albeit not all, studies reported higher energy expenditure in the luteal phase compared with follicular phase. Q10 of biological reactions lies between 2.0 and 3.0, predicting a 7‐12% increase in energy expenditure when body temperature rises by 1°C. In this study, temperature dependence of energy expenditure was assessed by comparing changes in sleeping energy expenditure and thermoregulation with menstrual cycle in 9 young females. Energy expenditure was measured using a metabolic chamber, in which sleep was recorded polysomnographically, and core body temperature and skin temperature were continuously monitored. Distal‐to‐proximal skin temperature gradient was assessed as an index of heat dissipation. In the luteal phase, a significant increase in average core body temperature (+0.27°C) and energy expenditure (+6.9%) were observed. Heat dissipation was suppressed during the first 2 hr of sleep in the luteal phase, compared with follicular phase. Rise in basal body temperature in the luteal phase was accompanied by increased energy expenditure and suppressed heat dissipation. The 6.9% increase in metabolic rate would require a Q10 of 12.4 to be attributable solely to temperature (+0.27°C), suggesting that energy expenditure in the luteal phase is enhanced through the mechanism, dependent and independent of luteal‐phase rise in body temperature presumably reflects other effects of the sex hormones. Abstract : Body temperature, heat production and heat dissipation during sleep was compared between follicular and luteal phase. During the luteal phase, significant increase in average core body temperature (+0.27°C) and energy expenditure (+6.9%) was observed, and temperature dependence of energy expenditure assessed as Q10 was 12.4. Heat dissipation was suppressed during the first 2 hr of sleep in the luteal phase, compared with follicular phase